2017
DOI: 10.18203/2320-6012.ijrms20170508
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional, multi-centric, epidemiology study to determine the prevalence of insomnia and related sleep habits in Indian hypertensive patients

Abstract: Background: Hypertension is a leading risk factor affecting mortality and disability-adjusted life years worldwide. The objective of the study was to determine the prevalence of insomnia, co-morbid medical conditions, lifestyle attributes, related sleep habits and sleep quality among Indian hypertensive patients.Methods: Adults (≥18 years) with newly diagnosed or known history of hypertension, willing to participate were enrolled in this cross-sectional, epidemiological study. Several variables including lifes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
2
1
1
Order By: Relevance
“…In the current study, the poor sleep quality was reported in 77.4% of hypertensive subjects which is quite high as compared to other studies in India (47.2%)[ 4 ] and Nigeria (42.4%)[ 18 ] in hypertensive population. The percentage of individuals with poor sleep quality was higher in our study because majority of them belong to stage 2 hypertension and a significant relationship had been found between sleep quality and stages of hypertension in our study and other studies too.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…In the current study, the poor sleep quality was reported in 77.4% of hypertensive subjects which is quite high as compared to other studies in India (47.2%)[ 4 ] and Nigeria (42.4%)[ 18 ] in hypertensive population. The percentage of individuals with poor sleep quality was higher in our study because majority of them belong to stage 2 hypertension and a significant relationship had been found between sleep quality and stages of hypertension in our study and other studies too.…”
Section: Discussioncontrasting
confidence: 67%
“…It has been shown that short sleep duration affects hypertension due to alteration in stress system function. [ 4 ] Another study suggested that sleep intervention showed insignificant improvement in 24 hour ambulatory systolic blood pressure. [ 5 ] Hypertension also affects the QOL due to its chronic nature with adverse effects on their physical, emotional and social well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Однако при ведении пациентов с АГ врачами общей практики, терапевтами, кардиологами практически не принимается во внимание возможное патогенное влияние на уровень АД процессов, непосредственно ассоциированных со сном. Инсомния часто выявляется у пациентов с АГ: по данным эпидемиологических исследований, частота инсомнии у этих пациентов составляет от 19 до 47,9% [13][14][15][16]. Частота инсомнии у больных АГ так же, как и в популяции в целом, больше у женщин и у лиц старших возрастных групп [16].…”
unclassified
“…Additionally, a total of 123 (18.7%) patients (of 657 patients) were newly diagnosed with hypertension, of which of 62 (50.4%) patients were insomniacs suggesting that insomnia is prevalent in newly diagnosed hypertensive patients. [ 15 ] Taylor et al . reported that the prevalence of hypertension is 43.1% in patients with insomnia as compared to 18.7% in individuals without insomnia.…”
Section: Resultsmentioning
confidence: 99%